2022
DOI: 10.1108/jadee-11-2021-0288
|View full text |Cite
|
Sign up to set email alerts
|

Herding and spillover effects in the Indian commodity futures market

Abstract: PurposeThe study examines herding in the Indian stock and commodity futures market including agricultural, metal and energy commodities. Herding is studied under various market conditions: rising and declining, high and low volatility. The study also examines spillover effects of herding.Design/methodology/approachThe study adapts the cross-sectional absolute deviation model given by Chang et al. (2000) to examine herding in Indian stock and commodity futures markets.FindingsThe results of the study indicate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 67 publications
(126 reference statements)
0
3
0
Order By: Relevance
“…This is prevalent in the US market, but disappeared in European and Asian markets during the SARS epidemic (Chang et al 2020). In a case study of herding in Indian energy commodity futures, Dewan and Dharni (2022) observed the absence of herding amongst energy commodity futures, except for downward market states, but reported a higher degree of herding behaviour for energy commodities during more volatile periods.…”
Section: Relationship Between Energy Markets and Herding In Bricsmentioning
confidence: 99%
“…This is prevalent in the US market, but disappeared in European and Asian markets during the SARS epidemic (Chang et al 2020). In a case study of herding in Indian energy commodity futures, Dewan and Dharni (2022) observed the absence of herding amongst energy commodity futures, except for downward market states, but reported a higher degree of herding behaviour for energy commodities during more volatile periods.…”
Section: Relationship Between Energy Markets and Herding In Bricsmentioning
confidence: 99%
“…and Huang , R.D., 1995) CH is then calculated using cross-sectional standard deviation (CSSD) and (Chang, 2000) CCK; after that, through cross-sectional absolute deviation (CSAD). The analysis of herding behavior under different market conditions, the bullish and bearish days analysis, and the joint analysis proposed (Chiang, Dazhi Zheng, 2010), Finally, as a joint analysis proposed (Lin Tan, Thomas C. Chiang, Joseph R. Mason, Edward Nelling,, 2008), demonstrate volatility differences with high and low volatility (Palak Dewan, Khushdeep Dharni, 2022). The study also examines whether asymmetric herd behavior in different market conditions.…”
Section: Dr Mohamed Hussien Abd El-razeek and Dr Ahmed Sayed Abd Elba...mentioning
confidence: 99%
“…In financial markets, herding behavior refers to the process by which market participants deduce information from the behavior of previous participants ([ 76 ]). Therefore, some studies cite herding behavior to explore the spillover effects in financial markets ([ 77 79 ]). Based on this background, our primary findings are as follows: First, the total liquidity spillovers during the GFC and COVID-19 periods were higher than those in the full period, proving that sectors were more connected in liquidity aspects during the crises.…”
Section: Introductionmentioning
confidence: 99%